DECENT WORK AND HUMAN DEVELOPMENT: INTERRELATION AND INTERDEPENDENCE - Olena Grishnova; Olena Brintseva (Izdevnieciba "Baltija Publishing", 2016)
The article theoretically investigates the interrelation between decent work and progress in human development and substantiates the connection statistically in the case study of Eastern European countries. Decent work foresees not only increase of educational and health opportunities, but also the human development revealed directly in the process of work, acquiring new knowledge and skills. Creating the conditions for productive employment is one of the most important areas of the decent work principles' implementation in the context of continuous human development, as well as expanding opportunities for high-quality education and healthcare.